Potential biomarkers associated with diabetic glomerulopathy through proteomics. (14th September 2015) - Hsu, Yung-Chien; Lei, Chen-Chou; Ho, Cheng; Shih, Ya-Hsueh; Lin, Chun-Liang
Abstract: Diabetic nephropathy (DN) is characterized by the development of progressive glomerulosclerotic lesions gradually leading to an increasing loss of functioning kidney parenchyma. Relatively little proteomic research of isolated glomeruli of experimental animal models has been done so far. Isolated glomerular proteomics is an innovative tool that potentially detects simultaneous expressions of glomeruli in diabetic pathological contexts. We compared the isolated glomerular profiles of rats with and without diabetes. The proteins in the aliquots of glomeruli were subjected to two-dimensional gel electrophoresis. The protein spots were matched and quantified using an imaging analysis system. The peptide mass fingerprints were identified by matrix-assisted laser desorption ionization time-of-flight mass spectrometry and a bioinformation search. We found that diabetes increased collagen type I and collagen type IV levels in diabetic glomeruli when compared to normal control group using Dynabeads. We found that rats with diabetes had significantly higher abundance of the Protein disulfide isomerase associated 3, Aspartoacylase-3, 3-hydroxymethyl-3-methylglutaryl-Coenzyme A lyase, Lactamase beta 2 and Agmat protein. However, diabetic glomeruli in rats had significantly lower levels of the Regucalcin, rCG52140, Aldo-keto reductase family 1, Peroxiredoxin 1, andl -arginine: glycine amidinotransferase. These proteins of interest were reported to modulate disturbances in the homeostasis of endoplasmic reticulum stress, disturbance of inflammatory and fibrinogenic activities, impairing endothelial function, and dysregulation in the antioxidation capacity/oxidative stress in several tissue types under pathological contexts. Taken together, our high-throughput isolated glomerular proteomic findings indicated that multiple pathological reactions presumably occurred in DN.